The design and development of a small size ozone chamber for rain harvesting - 274937 Khairul Anwar Omar; Zolkafle Buntat; Fakulti Kejuruteraan Elektrik (2008)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2008